The Effectiveness Multi-Level Marketing on Member Growth of Online Application "Minuha" in Lampung - Mukarson Aribowo; Anggalia Wibasuri (Prosiding International conference on Information Technology and Business (ICITB), 2020)
During the Covid-19 pandemic, any company must do an innovative idea to run a business and market the products. One of them is taking advantage of the MLM business strategy. There are many people who still have a negative stigma about MLM marketing strategies, even though MLM is a marketing strategy. In MLM, the seller benefits from product marketing and compensation from other salespeople under him who are recruited (downline). The MINUHA program is a masterpiece created by the nation's children to raise the economy of the Indonesian people, especially in Lampung through programs to be compiled on the Marketing Plan. Minuha application has 5 stars rating on google play store and it has been downloaded +500 times and has member growth with members of more than 200 people.Keywords      : Multi Level Marketing,Member Growth, Online Aplication “Minuha"